A comparative life cycle assessment of electric, compressed natural gas, and diesel buses in Thailand. (10th September 2021) - Gabriel, Natalie R.; Martin, Katherine K.; Haslam, Samantha J.; Faile, Julia C.; Kamens, Richard M.; Gheewala, Shabbir H.
Abstract: The public transportation system in Bangkok, Thailand relies on environmentally costly diesel buses that contribute daily to Bangkok's air quality problem. Two potential improvements to this highly polluting public transportation system are the implementation of electric or compressed natural gas buses. This paper analyzes the life-cycle environmental impacts using the ReCiPe life cycle impact assessment method (in Global warming, kg CO2 -eq, Stratospheric ozone depletion, kg CFC-11-eq, etc.), technical feasibility of implementation, and financial cost of implementing each bus type in Bangkok by calculating these metrics for a single bus and then scaling them to a fleet of that bus type. The entire life cycle of the buses as well as electric bus charging infrastructure is considered. It was found that shifting from diesel to electric or compressed natural gas buses would present a 54–55% or 37–41% decrease in overall damage to human and ecosystem health, an 88% or 80% decrease in resource depletion, and a 48% or 60% decrease in lifetime costs. If the entire diesel bus fleet in Bangkok of 14, 127 buses is converted to electric or compressed natural gas buses, the reduction of fine particle (PM2.5 ) transportation emissions would be approximately 21% and 18%. Of compressed natural gas and electric buses, compressed natural gas buses are the less expensive alternative, while electric buses cause less damage to the ecosystem, human health, and resource depletion. As the environmental impacts of electric buses depend on the regional electricity grid, electric buses also have the potential to further reduce environmental impacts with cleaner electricity production. Highlights: Bangkok air pollution significantly caused by transportation is a problem. Electric buses are better than CNG or diesel ones for environment and human health. CNG buses would be an improvement over diesel, fiscally and environmentally. PM2.5 emitted by diesel buses can be significantly reduced by alternative fuel use. Cleaner energy production is crucial for the success of an electric bus fleet.